2017
DOI: 10.1097/mib.0000000000001264
|View full text |Cite
|
Sign up to set email alerts
|

Guanylate Cyclase C Activation Shapes the Intestinal Microbiota in Patients with Familial Diarrhea and Increased Susceptibility for Crohnʼs Disease

Abstract: The findings support that the activating mutation in GUCY2C creates an intestinal environment with a major influence on the microbiota, which could contribute to the increased susceptibility to IBD in patients with FGDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 225 publications
(277 reference statements)
0
11
0
1
Order By: Relevance
“…We suggest that this early life susceptibility to STa-secreting ETEC is counter balanced by the critical role of GC-C in protecting the mucosa from non-STa producing, invasive bacterial pathogens, such as Salmonella . Concomitant with robust GC-C activity in the infant intestine is the colonization and expansion of commensal microflora and we suggest that additional studies will be necessary to determine if GC-C-regulated microflora complexity impacts susceptibility to invasive pathogen infection 20 , 25 , 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that this early life susceptibility to STa-secreting ETEC is counter balanced by the critical role of GC-C in protecting the mucosa from non-STa producing, invasive bacterial pathogens, such as Salmonella . Concomitant with robust GC-C activity in the infant intestine is the colonization and expansion of commensal microflora and we suggest that additional studies will be necessary to determine if GC-C-regulated microflora complexity impacts susceptibility to invasive pathogen infection 20 , 25 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…S2 ). Although therapeutic GC-C agonists have been extensively studied in the treatment of irritable bowel syndrome and chronic constipation, additional studies focusing on the impact of GC-C agonists on the bacterial microflora of the bowel, pathogenic or otherwise, is warranted 20 .…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent report that genetic GC-C activation influences the intestinal microbiota in patients with familial diarrhoea and increased susceptibility for Crohn’s disease, including increases in Enterobacteriaceae and loss of Bifidobacterium and Faecalibacterium prausnitzii ; the latter change is frequently associated with Crohn’s disease. 64 …”
Section: Biology Of the Gc-c Signalling Axismentioning
confidence: 99%
“…Ion transport across IECs may play an important role in the establishment and maintenance of the gut microbiota . Indeed, prominent depletion of Faecalibacterium and Bifidobacterium and an increase in Enterobacteriaceae have been described in patients with an activating mutation in GC‐C that is characterized by dysregulated intestinal ion transport, secretory diarrhea, and chronic mucosal inflammation . Independent studies have also reported alterations in the gut microbiota composition in GC‐C‐null mice and a decrease in the relative abundance of Lactobacillus spp., members of which have been implicated in inflammasome activation through caspase‐1‐dependent processing and release of IL‐1β by macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…These findings support an alternate model in which cyclic nucleotide signaling in enterocytes could regulate inflammasome activation by shaping the gut microbiota and modulating host–microbe cross talk. Thus, prolonged inflammasome activation may explain why chronic inflammation is seen in patients with activating mutations in GC‐C, with a considerable number of them diagnosed with Crohn's disease .…”
Section: Discussionmentioning
confidence: 99%